University physics students' ideas of thermal radiation expressed in open laboratory activities using infrared cameras. Issue 3 (3rd July 2017) - Haglund, Jesper; Melander, Emil; Weiszflog, Matthias; Andersson, Staffan
Abstract: Background : University physics students were engaged in open-ended thermodynamics laboratory activities with a focus on understanding a chosen phenomenon or the principle of laboratory apparatus, such as thermal radiation and a heat pump. Students had access to handheld infrared (IR) cameras for their investigations. Purpose: The purpose of the research was to explore students' interactions with reformed thermodynamics laboratory activities. It was guided by the research question: How do university physics students make use of IR cameras in open-ended investigation of thermal radiation as a phenomenon? Sample: The study was conducted with a class of first-year university physics students in Sweden. The interaction with the activities of four of the students was selected for analysis. The four students are males. Design and methods: We used a qualitative, interpretive approach to the study of students' interaction. The primary means of data collection was video recording of students' work with the laboratory activities and their subsequent presentations. The analysis focused on how IR cameras helped students notice phenomena relating to thermal radiation, with comparison to previous research on students' conceptions of thermal radiation. Results: When using the IR camera, students attended to the reflection of thermal radiation on shiny surfaces, such as polished metals, windows or a whiteboard and emissive properties of surfaces of different types. In this way, they went beyond using the technology as a temperature probe. Students were able to discuss merits and shortcomings of IR cameras in comparison with digital thermometers. Conclusions: With the help of IR cameras, university physics students attend to thermal phenomena that would otherwise easily go unnoticed.